Pembelajaran Cooperative Learning dengan Media Virtual untuk Meningkatkan Hasil Belajar Kewirausahaan Siswa SMK Kota Bekasi - Ari Wahyu Leksono; Maria Cleopatra; Sara Sahrazad; Sigit Widiyarto (Peneliti.net, 2020)
This study aims to describe the effect of cooperative learning and entrepreneurship learning outcomes in class VIII students of SMK Yadika Bekasi city. The population is 150 students. Sample of 26 students. used in the form of normality and homogeneity tests and using the t-test (One Sample t Test). The calculation uses SPSS 22. The research method used was experimental method. This study used an experimental design that was carried out in one group only without as many comparison groups (The One Group Pratest Posttest). Students can pack the product well. Students can improve vocational student learning outcomes. The results showed that the use of virtual cooperative learning methods was very effective in increasing entrepreneurial outcomes. . The use of virtual cooperative learning methods has a significant effect on entrepreneurial learning outcomes. After the use of virtual cooperatives, there is an increase in learning outcomes. It is recommended that teachers use this method, in order to reduce the level of boredom of students learning in class.